Long-term benefits of airway clearance in bronchiectasis: a randomised placebo-controlled trial. Issue 1 (11th January 2018) - Muñoz, Gerard; de Gracia, Javier; Buxó, Maria; Alvarez, Antonio; Vendrell, Montserrat
Keeping airways clear of mucus by airway clearance techniques seems essential in bronchiectasis treatment, although no placebo-controlled trials or any studies lasting longer than 3 months have been conducted. We evaluate the efficacy of the ELTGOL (slow expiration with the glottis opened in the lateral posture) technique over a 1-year period in bronchiectasis patients with chronic expectoration in a randomised placebo-controlled trial. Patients were randomised to perform the ELTGOL technique (n=22) or placebo exercises (n=22) twice-daily (ClinicalTrials.gov, NCT01578681). The primary outcome was sputum volume during the first intervention and 24 h later. Secondary outcomes included sputum volume during the intervention and 24 h later at month 12, exacerbations, quality of life, sputum analyses, pulmonary function, exercise capacity, systemic inflammation, treatment adherence, and side effects. Sputum volume during intervention and 24 h later was higher in the ELTGOL group than in the placebo group both at the beginning and end of the study. Patients in the ELTGOL group had fewer exacerbations (p=0.042) and a clinically significant improvement in the St George's Respiratory Questionnaire score (p<0.001) and the Leicester Cough Questionnaire score compared with the placebo group (p<0.001). Twice-daily ELTGOL technique over 1 year in bronchiectasis patients facilitated secretion removal and was associated with fewer exacerbations, improved quality of life, and reduced cough impact. The ELTGOL technique increases expectoration, reduces exacerbations and improves quality of life in bronchiectasis http://ow.ly/Q97C30gWVW4